Meaningful brands: A qualitative study on food waste management in the abattoir industry - Marebane, Susan (The IIE, 2020)
The issue of food waste is a universal problem, considering the extent to which many people are found to be food insecure. Food waste has a negative impact on natural resources, the economy and the environment as the practice of dumping at landfills is still frequently used as a method of waste disposal at many abattoirs. There is also a lack of documented data to quantify the extent of waste in the industry. This study explores the extent to which the waste management practices at abattoirs contribute to a meaningful brand. The study is non-empirical and employed a qualitative research method. Using the interpretivist paradigm, consumers provided input on their perceptions of abattoirs and their interpretation of a meaningful brand. Karan Beef provided input on the waste disposal methods currently being implemented in their operations. The waste management practices at the studied brand were found to contradict the literature, as Karan Beef repurposed their waste for secondary usage. The prominent themes found in the consumer research reveal that brand meaningfulness is a culmination of how the brand impacts the society, its people and the community. More studies can be conducted to assess the effectiveness of legislature in relation to waste management for better quantification to aid its implementation.
Keywords: Karan beef; Brand meaningfulness; Food industry; Food security